Pembuatan Media Pembelajaran Bahasa Inggris Menengah Atas Kelas X dengan Fitur Speaking dan Listening Practice Berbasis Android - Febby Anggreni Saek; Kristo Radion Purba; Anita Nathania Purbowo (Jurnal Infra, 2017)
English is a compulsory subject in all High Schools in Indonesia. In fact, English became one of the less favored subjects. Though English is a language needed in the world of work. Sometimes learning time and using textbooks make students bored and tired in learning English, so they need other media lo learn that more applicable.The implementation of this applications to help students learn English using the development of emerging technologies currently implemented on Android-based smartphones. With this application students can develop English abilities outside school. There are 18 chapters that become material of teaching materials with features of delivery of materials and quiz on the application of listening, speaking, drag and drop, multiple choice, and sound. Making learning media using Android SDK. The results showed that the program runs well on some kind of mobile device android with at least features kitkat 4.4 android. The application was also considered as interactive in terms of view application , delivery and module matter of about . This program also considered to be beneficial because it can help students learn without having to learn from books or their teachers.